3D bioprinted cancer cells are more tolerant to serum starvation than 2D cells due to autophagy. (June 2022) - Chen, H.; Liang, L.; Lin, Z.; Zhang, Y.; Mi, S.; Rao, L.; Xu, T.
Abstract: Cancer is a global issue and a serious threat to human health, one approach to treatment is starvation therapy. Recently, three-dimensional (3D) bioprinted tumor tissue models have been developed; however, whether 3D bioprinted models are good for in vitro study of starvation therapy is unclear. In this study, we studied the state of cells with serum-free medium in both 3D bioprinted scaffold and 2D cell cultures and found that 3D bioprinted cancer cells (3D cells) were more tolerant to serum starvation than 2D cells in terms of cell viability, cell proliferation, and M2 macrophage polarization. Moreover, the ratio of LC3II/I, an index of autophagy, increased much more in 3D cells, and 3D cells showed more autophagosomes than 2D cells after serum starvation, which indicated that the autophagy levels were higher in 3D cells. These results suggested that 3D cells are more tolerant to serum starvation than 2D cells, and autophagy may play an important role in this process. Graphical abstract: Image 1 Highlights: We studied if 3D bioprinted cancer models are good for starvation therapy. 3D bioprinted cancer cells are more tolerant to serum starvation than 2D cells. Autophagy may play an important role in this process.